Anti-caries evaluation of a nano-hydroxyapatite dental lotion for use after toothbrushing: An in situ study. (December 2021) - Amaechi, Bennett T.; Alshareif, Dina O.; Azees, Parveez A. Abdul; Shehata, Marina A.; Lima, Patricia P.; Abdollahi, Azadeh; Kalkhorani, Parisa S.; Evans, Veronica; Bagheri, Ariana; Okoye, Linda O.
Highlights: The application of 5% nanoHAP-containing dental lotion immediately following toothbrushing with 5% nanoHAP toothpaste:. enhanced the efficacy of 5% nanoHAP toothpaste in remineralizing initial caries lesions. may offer additional protection against tooth decay. The present study provides further evidence that the use of 5% nanoHAP toothpaste alone promotes caries remineralization. Abstract: Objectives: The aim of this randomized, double-blind, two-arm crossover in situ study was to investigate whether nano-hydroxyapatite (nanoHAP) dental lotion (Apagard Deep Care) applied immediately after tooth-brushing with nanoHAP toothpaste (Apagard M-plus) enhances the remineralization promotion and the demineralization inhibition efficacies of nanoHAP toothpastes. Methods: 64 sound enamel blocks and 64 blocks bearing artificially-produced initial caries were produced from human permanent molar teeth. During each treatment period, lasting 14 days per arm, two blocks, one sound and one lesion-bearing, were exposed to either 5% nanoHAP-containing or placebo dental lotion after tooth-brushing with 5% nanoHAP toothpaste, via an intra-oral appliance worn by 30 adults in each of the study groups. Baseline and post-test mineral loss were quantified using transverse microradiography (TMR). One-sided t -test of one group mean was used for intragroup comparison, while two-sided t -test of two independent means was used to compare the two dental lotions. Results: Pairwise comparison (baseline vs . post-test) indicated significant ( p <.001) remineralization by nanoHAP toothpaste in both groups. However, when compared against each other, there was a significantly ( p <.001) greater percentage of remineralization with nanoHAP lotion [58.4(±1.8)%] than with placebo lotion [37.7(±2.2)%]. TMR examination showed absolute demineralization inhibition in sound enamel blocks exposed to either lotions. Conclusions: Toothpaste containing 5% nanoHAP effectively remineralized initial caries and inhibited demineralization of healthy enamel; however, the application of a dental lotion containing 5% nanoHAP after brushing resulted in superior remineralization compared to a placebo lotion. Clinical Significance: Dental lotion containing 5% nanohydroxyapatite used immediately after toothbrushing with 5% nanohydroxyapatite toothpaste can serve as an adjunct to enhance the clinical benefits of the toothpaste.